Pengaruh Profitabilitas dan Transfer Pricing terhadap Penghindaran Pajak: Studi Pada Perusahaan Multinasional di Indonesia Periode 2019-2022 - Mustafa Zahri, Rihan; Wulan Sari, Erma; Safiria Ayu Ditta, Aliffianti; Nur Malinda, Indah (Jurnal Akuntansi, 2025)
Companies maximize profits for shareholder welfare, to increase profits Companies tend to avoid taxes in accordance with regulations to reduce the tax burden (Tax Avoidance). One of the tax avoidance practices by companies is transfer pricing. This study aims to test the effect of profitability on tax avoidance with transfer pricing as a moderating variable in 31 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. This test uses 124 company data samples using the purposive sampling method. The data analysis method uses multiple linear regression and the MRA (Moderated Regression Analysis) test. The results of this study indicate that profitability has a significant positive effect on company value, while the presence of the transfer pricing moderation variable proves that the profitability variable on tax avoidance is getting stronger because of the transfer pricing variable. Keywords: Profitability, Transfer pricing, Tax avoidance